The Role of the Kamsel Unit Through Dikmas Traffic in Minimizing Traffic Accidents Among High School and Equivalent Students at Jombang Police (Advances in Police Science Research Journal, 2024)
This research identifies the increasing traffic accidents among students in the jurisdiction of the Jombang Police Resort, which requires preventive action through Traffic Education for the Community (Dikmas Lantas). The role of the Kamsel Unit in Dikmas Lantas is considered crucial as an effort to prevent traffic accidents among high school students in Jombang Regency. The purpose of this study is to understand the role of the Kamsel Unit in minimizing traffic accidents among high school students in the jurisdiction of the Jombang Police Resort. This research is qualitative, using theories of organizational resources, human resources, POAC management, and competence, referring to the police operational guidelines related to Traffic Education for the Community. The results show that the organizational resources of the Kamsel Unit in the Jombang Police Resort face challenges, especially in terms of the quantity and quality of personnel, as well as the lack of clear task allocation in the organization. The researcher concludes that the role of the Kamsel Unit in minimizing traffic accidents among high school students in the Jombang Police Resort is not yet optimal, and suggests that Kamsel personnel improve their competencies through interpersonal skills training and receive assistance from other units in implementing Dikmas Lantas.
Keywords: Unit Kamsel, Dikmas Lantas, Kecelakaan Lalu Lintas, Pelajar SMA Sederajat